1996
DOI: 10.1063/1.361400
|View full text |Cite
|
Sign up to set email alerts
|

Deflagration-to-detonation transition in granular pentaerythritol tetranitrate

Abstract: The deflagration-to-detonation transition process has been observed in pressed granular columns of the explosive pentaerythritol tetranitrate. Charges were confined within a steel housing which had been fitted with a polycarbonate window to allow direct recording by high-speed streak photography. The explosive was thermally ignited by a gasless pyrotechnic mixture to minimize pre-pressurization of the charge. The results indicate that upon ignition, early choked flow of the combustion gases prevents the contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…This and other research studies on DDT have largely been motivated by concerns over the increased sensitivity of damaged high explosives and propellants to mechanical impact. Experiments have shown that weak mechanical shock (∼0.2 GPa) is often sufficient to initiate detonation in granulated energetic material through various mechanisms of hot-spot formation [34,36,53], whereas only strong shocks (>10 GPa) provide sufficient energy to initiate detonation in cast material. Here, we first briefly introduce the physical problem, focusing on issues relevant to the numerical solution of two-phase DDT models, and then describe a new high-resolution numerical method for accurately solving these models.…”
Section: Introductionmentioning
confidence: 99%
“…This and other research studies on DDT have largely been motivated by concerns over the increased sensitivity of damaged high explosives and propellants to mechanical impact. Experiments have shown that weak mechanical shock (∼0.2 GPa) is often sufficient to initiate detonation in granulated energetic material through various mechanisms of hot-spot formation [34,36,53], whereas only strong shocks (>10 GPa) provide sufficient energy to initiate detonation in cast material. Here, we first briefly introduce the physical problem, focusing on issues relevant to the numerical solution of two-phase DDT models, and then describe a new high-resolution numerical method for accurately solving these models.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent application to 180 mm PETN powder at 21 % porosity had the advantage of both SDT tests [34, p310-315] and DDT tests [43] at the same porosity. The speed of the ignition front through that powder, and the particle size distribution around the 180 mm mean value were not measured, and the calculations [44] showed the sensitivity of the calculated transition distance to estimated value ranges of those parameters.…”
Section: Deflagration-to-detonation Transition (Ddt)mentioning
confidence: 99%
“…We will apply the all-porosity CREST model to calculations of the DDT transition distance as a function of porosity. It is possible that the PETN experiments [43] would be suitable candidates, because SDT and DDT tests have been performed at several overlapping porosities.…”
Section: Future Applicationsmentioning
confidence: 99%
“…7 The confinement is effectively sealed against venting of gaseous products by polycarbonate and aluminum plugs. The pyrotechnic igniter used was an 80% potassium dichromate, 20% amorphous boron mixture.…”
Section: A Photographymentioning
confidence: 99%
“…Postmortem examination of the confinement shows a correlation between the light region on the confinement and the region in which the compacted plug reached its critical parameters between B and C. This correlation has been previously been made by other researchers. 1,7 B. Ultrafine PETN Figure 5 shows a streak record of a deflagration-tolocalized thermal explosion detonation transition ͑DXDT͒ type process occurring in a charge of micron grain size PETN pressed to a density of 29% TMD. A schematic of the confinement is shown next to the streak record at the same scale as the photograph.…”
Section: A Conventional Petnmentioning
confidence: 99%